An Analysis of the Temporomandibular Joint Range of Motion and Related Factors in Children and Adolescents - YounJung Park; Taeyang Lee; Minkyeong Seog; Seong-Oh Kim; Joohee Kim; Jeong-Seung Kwon; Chung-Min Kang (MDPI AG, 2021)
This study was designed to establish safe guidelines for pediatric dental practice regarding temporomandibular joint (TMJ) range of motion (ROM) and mouth area (MA). A total of 438 children aged 3-15 years old of homogenous ethnicity participated in the study; the distribution of participants was approximately equal (sex; n = 15; age, n = 30). Maximum mouth opening (MMO), body height, weight, and age of each participant were recorded, and the TMJ ROM including anterior and lateral movements, MA, and mouth width were documented. Males showed higher mouth width, MMO, and MA values than females. MMO and MA increased with age, height, and weight in a statistically significant manner. MMO of 40 mm is reached by the age of 5.2 years, at a height of 105.9 cm and a weight of 18.6 kg. MMO showed a moderate correlation with age, height, weight, and mouth width, and MA moderately correlated with mouth width. Anterior and lateral movements did not show any close relation to these aforementioned factors. The findings of this study suggest that forcible mouth opening over 40 mm should be more cautiously considered, especially in children shorter than 105 cm, lighter than 18 kg and in children under 5 years old.